Neoandrographolide inhibits mature osteoclast differentiation to alleviate bone loss and treat osteoporosis - Tang, Kai; Deng, Wei; Huang, Zhiying; Chen, Simin; Zhu, Zilin; Lin, Shukun; Zhong, Lubin; Zheng, Quanxin; Zhao, Wenhua; Zhang, Zhida; Mo, Ling (Frontiers in Pharmacology, 2025)
BackgroundOsteoporosis (OP), as the prevalent systemic metabolic bone disease worldwide, progresses insidiously and slowly. The clinical discomfort and complications associated with OP impose a significant burden on patients. Therefore, finding more effective treatments for OP remains an urgent challenge.MethodWe first conducted in vitro experiments to determine whether Neoandrographolide (NEO) exhibits cytotoxic or proliferative effects on bone marrow macrophages (BMMs) and to explore the specific timeframe during which NEO exerts its inhibitory action on osteoclast (OC) differentiation. Through Reverse Transcription Polymerase Chain Reaction (RT-PCR) and Western blot analysis, we examined the relative expression levels of genes and proteins associated with OC differentiation like CTSK,c-Fos,MMP9,NFATc1, and verified the underlying mechanisms. Finally, we performed in vivo experiments to further investigate the inflammation.ResultsNEO exhibits no significant cytotoxic effects on BMMs at concentrations less than or equal to 30 μM while exerting inhibitory effects on OC differentiation during its early and middle stages. RT-PCR and Western blot results reveal that NEO suppresses the expression of genes and proteins including CTSK,c-Fos,MMP9,NFATc1. Western blot findings also indicate that NEO inhibits the phosphorylation of ERK, P38, JNK, and P65 but does not reverse the degradation of IκB-α. Additionally, NEO affects the phosphorylation of proteins in the PI3K/AKT, GSK3β, and PPARγ signaling pathways, demonstrating that NEO can inhibit OC formation through multiple pathways and targets. In vivo experiments further validated the in vitro findings by constructing an OP model, showing that NEO can mitigate bone loss induced by OC differentiation.ConclusionNEO has the potential to serve as a therapeutic agent for OP by targeting multiple sites and inhibiting the formation of mature OC through various signaling pathways.